Activity of swallowing‐related neurons in the medulla in the perfused brainstem preparation in rats. (8th November 2018) - Hashimoto, Keiko; Sugiyama, Yoichiro; Fuse, Shinya; Umezaki, Toshiro; Oku, Yoshitaka; Dutschmann, Mathias; Hirano, Shigeru
Abstract : Objectives/Hypothesis: We aimed to investigate and validate the cellular activity patterns and the potential topographical organization of neurons of the medullary swallowing pattern generator (Sw‐CPG). We used the perfused brainstem preparation as an innovative experimental model that allows for stable neuronal recording in the brainstem. Study Design: Animal model. Methods: Experiments were conducted in 14 juvenile Wistar rats. The activities of the phrenic, vagus, and hypoglossal nerves were recorded at baseline, and fictive swallowing was elicited by stimulation of the superior laryngeal nerve. Extracellular action potentials of 72 swallowing‐related neurons were recorded in the Sw‐CPG of the dorsal medulla oblongata. Results: Neurons could be classified into three types: sensory relay, and neurons that were excited or inhibited during fictive swallowing. Approximately one‐third of the neurons likely received monosynaptic input from the laryngeal afferents. One‐third of neurons recorded showed respiratory‐related activity, most of which exhibited inspiratory modulation. The neurons were widely distributed in the nucleus tractus solitarius and reticular formation. Conclusions: The perfused brainstem preparation of rat fully preserves the Sw‐CPG. The recorded cellular activities and general topographical organization of swallowing neurons are in accordance with previous in vivo studies. Thus, the perfused brainstem preparation is an ideal experimental model to advance the understanding of neuronal mechanisms underlying swallowing. Level of Evidence: NA Laryngoscope, 129:E72–E79, 2019